Modern Organizational and Economic Mechanism for Environmental Safety - LUTKOVSKA, Svitlana; KALETNIK, Grygorii (Journal of Environmental Management and Tourism; Vol 11 No 3 (2020): JEMT Volume XI Issue 3(43) Summer 2020DO - 10.14505//jemt.11.3(43).14, 2020)
In this article, the organizational and economic mechanism of security management is part of the overall system of the economy as a whole with its peculiarities. It is established that the purpose of organizational and economic mechanism of management of natural, anthropogenic and ecological safety is to harmonize economic and environmental interests of social production: vertical - state, regional, local, horizontal - territorial, departmental, at the level of relations between enterprises, etc., as well as establishing an effective security assurance procedure. The objective of the organizational and economic management mechanism is to strengthen and enhance the natural, anthropogenic and ecological security of the country, under the following conditions: to function within the current legal framework; to provide reliable protection of national and regional interests in the field of guaranteeing natural anthropogenic and ecological security; create conditions for forecasting and timely prevention of threats and adverse processes of security compliance; be effective in both normal and emergency situations; be determined by a clear structure and functional separation of the authorities. It is confirmed that the organizational and economic mechanism of environmental safety is based on the following principles: scientific validity, economic responsibility, complexity, economic calculation, payment for the use of natural resources. The structure of the economic mechanism of nature management and nature conservation activity is developed. The classification of economic instruments for guaranteeing environmental safety has been formed. The modern organizational and economic mechanism of ecological safety has been developed, which provides the process of functioning of ecological safety and is supported by the legal, organizational, technical, socio-cultural and informational components. It is proved that the economic component of the organizational and economic mechanism determines the preconditions for the functioning of financial and economic relations between the participants of the process of guaranteeing environmental safety. The effectiveness of the economic subsystem is ensured by close interaction and interaction with the organizational, through the institutionalization of the components of the system and mechanisms of their organizational interaction: subordination, powers, rights, responsibilities, regularity and forms of organizational relations.